2020
DOI: 10.1590/1678-7757-2019-0042
|View full text |Cite
|
Sign up to set email alerts
|

The use of a liner under different bulk-fill resin composites: 3D GAP formation analysis by x-ray microcomputed tomography

Abstract: Gap formation of composite resin restorations is a serious shortcoming in clinical practice. Polymerization shrinkage stress exceeds the tooth-restoration bond strength, and it causes bacterial infiltration within gaps between cavity walls and the restorative material. Thus, an intermediate liner application with a low elastic modulus has been advised to minimize polymerization shrinkage as well as gap formation.Objective:The purpose of this in vitro study was to assess gap formation volume in premolars restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
2
17
0
1
Order By: Relevance
“…In addition, the unique flexible nature of the material allows for expansion and contraction of the resin restorative without opening the cavo-surface margins. 10,24,25 Current study results came in agreement with El Sayed et al 16 who compared "self-etch" to "etch and rinse" systems, as they concluded that "etch and rinse"adhesive deserved its position as the gold standard bonding agent, as it showed less microleakage. On the contrary, Gupta et al 26 , evaluated microleakage with different systems, and they came to the conclusion that one step self-etch adhesives revealed less microleakage than total etch ones.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the unique flexible nature of the material allows for expansion and contraction of the resin restorative without opening the cavo-surface margins. 10,24,25 Current study results came in agreement with El Sayed et al 16 who compared "self-etch" to "etch and rinse" systems, as they concluded that "etch and rinse"adhesive deserved its position as the gold standard bonding agent, as it showed less microleakage. On the contrary, Gupta et al 26 , evaluated microleakage with different systems, and they came to the conclusion that one step self-etch adhesives revealed less microleakage than total etch ones.…”
Section: Discussionsupporting
confidence: 84%
“…1 This could result from polymerization shrinkage stress of the composite resins; the stress overcomes the bond strength of restoration causing the passage of fluids and bacterial infiltration between walls of the cavity and filling material. 2 The presence or absence of microleakage is one of the outcomes accountable for the success of fillings overtime 3 ; oral microorganisms invade the tooth-restoration gap in a short time and they can reach dental tissues causing a biological damage. 4 The microleakage could result in discoloration 5 of the margins of restoration, dentin hypersensitivity, secondary caries, and also pulp affections.…”
Section: Introductionmentioning
confidence: 99%
“…11 Although bulk-fill composite resins are claimed to exhibit low polymerization shrinkage, there are not enough evidences concerning the effects of gap formation of these composites using an intermediate liner. 2 This systematic review with meta-analysis aimed: • To evaluate the difference of microleakage between dental restorations performed with bulk-fill and conventional composites resins. • To assess the entity of marginal discoloration, marginal adaptation, and secondary caries of restorations made by the two different composites resins.…”
Section: Introductionmentioning
confidence: 99%
“…However, the marginal adaption of RDMs in class I and class II cavities reflects complex interactions between adhesive bonding on one hand 25 , and PSS at the tooth-restoration interface on the other 32 . The level of PSS and debonding are more probably dependent upon the shape and hence constraints of the cavity 8,9,33,34 , as well as viscoelastic properties of RDMs 35,36 , than other factors. It is well-known that cavity configuration (C-factor) is one of the main factors affecting the development of PSS 8,9,33,37 , since greater confinement imposed on the RDM leaves a smaller number of free surfaces for resin composite shrinkage and PSS relaxation.…”
Section: Discussionmentioning
confidence: 99%